Analisa Persepsi Risiko terhadap Niat Wisata dan Persyaratan Tes Covid-19 di Indonesia - Pranindyasari, Chelsia; Siswomihardjo, Sari Winahjoe; Armielia, Adestya Ayu (Universitas Pendidikan Ganesha, 2023)
The global pandemic of Covid-19, including Indonesia, impacted limited mobility and caused several industrial sectors crises. Industries with direct contact have an enormous impact, such as tourism, which has suffered losses due to a decrease in foreign tourists. The disadvantages can be overcome by developing the intention to visit domestic tourists. This study was conducted to analyze the willingness to pay for travel requirements in Indonesia and the impact of the perceived risk of traveling on travel intentions used Theory Planned Behavior (TPB). Structural equation modeling was used on seven hypotheses measured by 246 respondents. The results of this study indicate that the intention to travel is influenced by the willingness to pay for travel requirements through three variables the perception of risk, positive travel attitudes and perceived behavioral control. This study advises the government to increase health consciousness and the importance of Covid-19 tests to reduce the spread. The tourism industry can provide promotions by showing trust and low risk that the trip will be fun, positive, and accessible